ChemInform Abstract: Generation of Hydrogen from Zero‐Valent Iron and Water: Catalytic Transfer Hydrogenation of Olefins in Presence of Pd/C. Issue 11 (February 2016) - Patil, Rajendra D.; Sasson, Yoel
Abstract: In the mild protocol developed, water functions as the hydrogen source.